Nanotechnology Approaches for Chloroplast Biotechnology Advancements - Newkirk, Gregory M.; de Allende, Pedro; Jinkerson, Robert E.; Giraldo, Juan Pablo (Frontiers in Plant Science, 2021)
Photosynthetic organisms are sources of sustainable foods, renewable biofuels, novel biopharmaceuticals, and next-generation biomaterials essential for modern society. Efforts to improve the yield, variety, and sustainability of products dependent on chloroplasts are limited by the need for biotechnological approaches for high-throughput chloroplast transformation, monitoring chloroplast function, and engineering photosynthesis across diverse plant species. The use of nanotechnology has emerged as a novel approach to overcome some of these limitations. Nanotechnology is enabling advances in the targeted delivery of chemicals and genetic elements to chloroplasts, nanosensors for chloroplast biomolecules, and nanotherapeutics for enhancing chloroplast performance. Nanotechnology-mediated delivery of DNA to the chloroplast has the potential to revolutionize chloroplast synthetic biology by allowing transgenes, or even synthesized DNA libraries, to be delivered to a variety of photosynthetic species. Crop yield improvements could be enabled by nanomaterials that enhance photosynthesis, increase tolerance to stresses, and act as nanosensors for biomolecules associated with chloroplast function. Engineering isolated chloroplasts through nanotechnology and synthetic biology approaches are leading to a new generation of plant-based biomaterials able to self-repair using abundant CO2 and water sources, and powered by renewable sunlight energy. Current knowledge gaps of nanotechnology-enabled approaches for chloroplast biotechnology include precise mechanisms of entry into plant cells and organelles, limited understanding about nanoparticle-based chloroplast transformations, and the translation of lab-based nanotechnology tools to the agricultural field with crop plants. Future research in chloroplast biotechnology mediated by the merging of synthetic biology and nanotechnology approaches can yield tools for precise control and monitoring of chloroplast function in vivo and ex vivo across diverse plant species, allowing increased plant productivity and turning plants into widely available sustainable technologies.